Pusa hispida subsp. hispida Schreber 1775 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Pusa hispida subsp. hispida Schreber 1775 Pusa hispida subsp. hispida Schreber 1775, Die Saugethiere, Vol. 2, 13: pl. 86 [1775]; see also text 3 (17): 312 [1776]. Type Locality: "Man fängt ihn auf den Küsten von Grönland und Labrader". Synonyms: Pusa hispida subsp. annellata (Nilsson 1820); Pusa hispida subsp. beaufortiana (Anderson 1943); Pusa hispida subsp. birulai (Smirnov 1929); Pusa hispida subsp. foetica (Fabricius 1776); Pusa hispida subsp. krascheninikovi (Naumov and Smirnov 1936); Pusa hispida subsp. pomororum (Smirnov 1929); Pusa hispida subsp. pygmaea (Zukowsky 1921); Pusa hispida subsp. rochmistrovi (Smirnov 1929); Pusa hispida subsp. soperi (Anderson 1943). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Carnivora, pp. 532-628 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 600, DOI: 10.5281/zenodo.7316519